Creative arts therapies as temporary home for refugees: insights from literature and practice - Dieterich-Hartwell, Rebekka; Koch, Sabine C. (Behavioral Sciences, 2017)
One of the frequently overlooked psychosocial problems of refugees is the phenomenon of homesickness. Being forced into exile and unable to return home may cause natural feelings of nostalgia but may also result in emotional, cognitive, behavioral and physical adversities. According to the literature, the creative arts therapies with their attention to preverbal language—music, imagery, dance, role play, and movement—are able to reach individuals through the senses and promote successive integration, which can lead to transformation and therapeutic change. These forms of therapy can be a temporary home for refugees in the acculturation process, by serving as a safe and enactive transitional space. More specifically, working with dance and movement can foster the experience of the body as a home and thus provide a safe starting place, from which to regulate arousal, increase interoception, and symbolize trauma- and resource-related processes. Hearing, playing, and singing music from the home culture may assist individuals in maintaining their cultural and personal individuality. Creating drawings, paintings, or sculpturing around the topics of houses and environments from the past can help refugees to retain their identity through art, creating safe spaces for the future helps to look ahead, retain resources, and regain control. This article provides a literature review related to home and homesickness, and the role the arts therapies can play for refugees in transition. It further reports selected interview data on adverse life events and burdens in the host country from a German study. We propose that the creative arts therapies are not only a container that offers a temporary home, but can also serve as a bridge that gently guides refugees to a stepwise integration in the host country. Several clinical and research examples are presented suggesting that the support and affirmation through the creative arts can strengthen individuals in their process of moving from an old to a new environment.